2016
DOI: 10.1111/age.12508
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide proteomics analysis on longissimus muscles in Qinchuan beef cattle

Abstract: To gain further insight into the molecular mechanism of bovine muscle development, we combined mass spectrometry characterization of proteins with Illumina deep sequencing of RNAs obtained from bovine longissimus muscle (LD) at prenatal and postnatal stages. For the proteomic study, each group of LD proteins was extracted and labeled using isobaric tags for relative and absolute quantitation (iTRAQ) method. Among the 1321 proteins identified from six samples, 390 proteins were differentially expressed in embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In our study, we found several genes within ROH hotspots, which have been previously reported under selection in cattle 4045 . Among them, we identified Heat Shock Protein Family A (Hsp70) Member 9 ( HSPA9 ) in seven Chinese local breed, this gene is immune-related genes, and also shows differentially expressed during bovine muscle development 46 . Previous studies suggested that HSPA9 abundance in muscle had positive correlation with beef tenderness 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found several genes within ROH hotspots, which have been previously reported under selection in cattle 4045 . Among them, we identified Heat Shock Protein Family A (Hsp70) Member 9 ( HSPA9 ) in seven Chinese local breed, this gene is immune-related genes, and also shows differentially expressed during bovine muscle development 46 . Previous studies suggested that HSPA9 abundance in muscle had positive correlation with beef tenderness 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain high quality meat, researchers have conducted some studies to address these complex issues. The connections between beef quality and number and size of fiber have been examined by Mao et al (2016), the relation between the growth of cattle and beef quality is studied by He et al (2017). The impacts of manufacturing and storage means, as well as stock fodder on quality and a comparison between the quality of Angus beef and other variety of cattle have also been analyzed (Taye et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Isobaric tagging for relative and absolute quantification (iTRAQ) is a recently developed method for the quantitative analysis of proteomes that can identify proteins and provide more accurate quantitative measurements of protein abundance than traditional two-dimensional electrophoresis analysis [8]. The iTRAQ method has been widely applied to investigate the proteomes of cattle [9], chicken [10], and pig [11]. Previous proteomics studies using iTRAQ have focused on muscle development [11], embryo development [12], meat tenderness [10], and lipid deposition [13] in livestock and poultry.…”
Section: Introductionmentioning
confidence: 99%